2000
DOI: 10.1021/ie000074j
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Feed Vaporization in Fluid Catalytic Cracking

Abstract: Feed vaporization in the fluid catalytic cracking (FCC) process affects the yield of valuable products in risers and downers. Feedstock droplets sprayed into a fluid cracker undergo both homogeneous vaporization in the gas phase and heterogeneous vaporization as they collide with catalyst particles. This paper models both processes. Homogeneous vaporization, with both convection and radiation heat transfer, cannot completely vaporize oil droplets with diameters larger than 10 μm. Spraying droplets into a dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…This model predicted order of magnitude faster evaporation rates. Mirgain et al (2000) used the concept but distinguished three different types of collisions. The first particle to be hit by the droplet gets covered with liquid.…”
Section: Brief Review Of Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This model predicted order of magnitude faster evaporation rates. Mirgain et al (2000) used the concept but distinguished three different types of collisions. The first particle to be hit by the droplet gets covered with liquid.…”
Section: Brief Review Of Previous Workmentioning
confidence: 99%
“…This type of collision is referred to as impact with transfer. Mirgain et al (2000) applied the approach of Buchanan (1994). The vaporization time was then estimated from the time needed for the liquid to impact enough particles.…”
Section: Brief Review Of Previous Workmentioning
confidence: 99%
“…On contrary to the theory proposed by Martin (1990) and Buchanan (1994), Mirgain et al (2000) argued that Leidenfrost effect possibly does not occur during droplet-particle collision in FCC riser primarily because of high Weber number (We > 5000) of the injected droplets. They reasoned since critical We number for droplets is reported to be 80 in Leidenfrost regime (Wachters and Westerling, 1966), droplet must break under this condition.…”
Section: Introductionmentioning
confidence: 62%
“…They reasoned since critical We number for droplets is reported to be 80 in Leidenfrost regime (Wachters and Westerling, 1966), droplet must break under this condition. Mirgain et al (2000) also critically analyzed the effect of homogeneous and heterogeneous heat transfer modes on the vaporization time in FCC riser and showed that within the typical residence time in a riser, complete vaporization of the feedstock is not possible if only the homogeneous mode is considered. The residence time in an industrial scale FCC riser is usually defined as the time since the feed is injected into the bottom of the riser reactor until the product vapours comes out at the top of the riser.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation